INDUSTRIAL DEVELOPMENTS, AUTOMATION BENEFITS AND ROBOTIC MARKET OUTLOOK IN BRAZIL AND THE WORLD - Fenerick, Jessica Aparecida; Volante, Carlos Rodrigo (Revista Interface Tecnológica, 2020)
This article is a study of how industries evolved since the beginning of the industrial revolution and how the robotics market is distributed around the world, such as which sectors stood out in Brazil. The industrial revolution that started in the 18th century was extremely important for capitalism, economics, the evolution of technologies and for inventions that were emerging. The new technologies generate great impacts on the industrial environment, thus being able to generate benefits and changes in the workforce, and when adhering to these new technologies the companies seek to increase the efficiency and effectiveness in their processes, and consequently, increase the safety of the workers because, it decreases direct contact and repetitive movements. So this article was written with the aim of demonstrating how industries have evolved, the benefits of automation and the prospects of the robotics market. The number of robots around the world has been growing a lot and the world powers stand out for the quantity produced and installed, Brazil’s participation in this scenario is evidenced by how much it still needs to evolve to reach the most advanced countries in technologies and finally discuss its benefits. Qualitative bibliographic research was used based on the collection of data obtained from books and scientific articles by electronic means. The results of the work indicate that the investment in automation is of great advantage for the industries, as they increase the productivity, quality and safety of the worker.